Asia‐Pacific guidelines for managing functional dyspepsia overlapping with other gastrointestinal symptoms. Issue 2 (28th November 2022) - Gwee, Kok‐Ann; Lee, Yeong Yeh; Suzuki, Hidekazu; Ghoshal, Uday Chand; Holtmann, Gerald; Bai, Tao; Barbara, Giovanni; Chen, Min‐hu; Chua, Andrew Seng Boon; Gibson, Peter R; Hou, Xiaohua; Liu, Jinsong; et al.
Abstract: Contemporary systems for the diagnosis and management gastrointestinal symptoms not attributable to organic diseases (Functional GI Disorders, FGID, now renamed Disorders of Gut‐Brain Interaction, DGBI) seek to categorize patients into narrowly defined symptom‐based sub‐classes to enable targeted treatment of patient cohorts with similar underlying putative pathophysiology. However, an overlap of symptom categories frequently occurs and has a negative impact on treatment outcomes. There is a lack of guidance on their management. An Asian Pacific Association of Gastroenterology (APAGE) working group was set up to develop clinical practice guidelines for management of patients with functional dyspepsia (FD) who have an overlap with another functional gastrointestinal disorder: FD with gastroesophageal reflux (FD‐GERD), epigastric pain syndrome with irritable bowel syndrome (EPS‐IBS), postprandial distress syndrome with IBS (PDS‐IBS), and FD‐Constipation. We identified putative pathophysiology to provide a basis for treatment recommendations. A management algorithm is presented to guide primary and secondary care clinicians.